Impact of fatigue on activities of daily living in patients with rheumatoid arthritis - Khaled Abdulwahab Amer; Mansour Somaily; Abdulrahman Ali Aldosari; Lujane Mohammed Al-Tarish; Sereen Dhafer Al-Muhsin; Muhammed Alhussain Alkhairi; Fahad Saeed Thamer Alahmari; Abdussalam Mohammed A. Alqhtani (Medicine, 2026)
Fatigue is a prevalent and disabling feature of rheumatoid arthritis (RA) that interferes with everyday tasks and overall quality of life. Evidence on how RA-related fatigue affects activities of daily living (ADL) in Middle Eastern, and particularly Saudi Arabian, populations is sparse. This study aimed to quantify fatigue severity in patients with RA seen at a tertiary center in the Aseer region and examine its relationship with disease activity and ADL, using the Bristol RA Fatigue Multidimensional Questionnaire (BRAF-MDQ). We carried out a single-center, cross-sectional study with prospective data collection at the rheumatology outpatient clinics of Aseer Central Hospital, Saudi Arabia, between March and December 2024. Adults aged 16 years or older with RA, classified according to the 2010 American College of Rheumatology–European Alliance of Associations for Rheumatology criteria, were enrolled consecutively by convenience sampling. Fatigue was rated with the Arabic version of the BRAF-MDQ; disease activity was scored with the Disease Activity Score in 28 joints using C-reactive protein (DAS28-CRP); and functional status was captured with a validated 12-item ADL score. Independent-samples t -tests, Spearman rank correlation, and multivariable linear regression were performed in International Business Machines Statistical Package for the Social Sciences Statistics version 22 (IBM Corp.). A total of 140 patients were analyzed (82.1% women; mean age 47 years). Women had higher global BRAF-MDQ scores than men (46.1 vs 32.2; P < .001), with the difference driven mainly by the physical and emotional subscales. Patients in the high-fatigue group showed substantially greater ADL impairment than those in the low-fatigue group (10.64 ± 7.45 vs 3.42 ± 2.54; P < .001). BRAF-MDQ scores correlated strongly with both DAS28-CRP ( ρ = 0.932–0.989) and ADL ( ρ = 0.879–0.992). In the multivariable model, DAS28-CRP ( β = 0.055; 95% confidence interval, 0.040–0.070) and ADL ( β = 0.042; 95% confidence interval, 0.030–0.054) were each independently and positively associated with global fatigue. In this Saudi cohort, fatigue in RA was widespread and tracked closely with both disease activity and impairment of daily activities, with women reporting heavier burden in unadjusted comparisons. Routine fatigue assessment, together with evidence-based non-pharmacological strategies, should be embedded into the ambulatory care of patients with RA.